Development of high-throughput UPLC-MS/MS using multiple reaction monitoring for quantitation of complex human milk oligosaccharides and application to large population survey of secretor status and Lewis blood group. (15th December 2022) - Li, Jiaqi; Bi, Ye; Zheng, Yi; Cao, Cuiyan; Yu, Long; Yang, Zhenyu; Chai, Wengang; Yan, Jingyu; Lai, Jianqiang; Liang, Xinmiao
Graphical abstract: Highlights: High-throughput method for absolute quantitation of 23 HMOs including isomers. Large population survey of oligosaccharides in milk of 251 Chinese mothers. Simultaneous assignment of secretor status and Lewis blood phenotypes. Variation in HMOs from donors of five ethnic groups living in different areas. Abstract: Human milk oligosaccharides (HMOs) have attracted increasing attention due to the emerging evidence of their positive roles for infant's health. A high-throughput method for absolute quantitation of the complex HMOs including multiple isomeric structures is important but very challenging, due to the highly divers nature and wide variation in content of HMOs from different individuals. Here we used UPLC-MS-MRM in the negative-ion mode for accurate quantitation of 23 complex HMOs in just 15 min. The selected oligosaccharides are in their native forms and include neutral and sialylated, fucosylated and non-fucosylated, linear and branched, and secretor and Lewis phenotype indicators. The well validated method with good sensitivity, recovery and reproducibility was then applied to a large population quantitative survey of 251 Chinese mothers from five different ethnic groups (Han, Zhuang, Hui, Mongolian and Tibetan) living in different geographical regions for their secretor's status and Lewis phenotypes.